Fecal calprotectin levels in patients with fibromyalgia: A cross-sectional study - Ece Çınar,; Meryem Burcu Türkoğlu Aytar,; Musa Baklacı,; Simin Hepgüler,; Burcu Barutçuoğlu, (Archives of Rheumatology, 2024)
Objectives: This study aimed to evaluate levels of fecal calprotectin (FC), a biomarker that helps distinguish irritable bowel syndrome from inflammatory gut disorders, in patients with fibromyalgia syndrome (FMS) and compare them to healthy controls. Patients and methods: The cross-sectional study was carried out on patients diagnosed with FMS according to the ACR (American College of Rheumatology) 2016 classification and healthy controls between January 2021 and February 2022. FMS patients were grouped according to the absence (Group 1) or presence (Group 2) of gastrointestinal symptoms. A third group of healthy controls without gastrointestinal complaints (Group 3) was included. Demographic data, comorbidities, medications, symptom severity scale, and widespread pain index scores were recorded. All subjects were asked to provide stool samples for the measurement of FC levels. Results: A total of 100 subjects were included in the study. There were 33 patients (4 males, 29 females, mean age: 46.9±10.6; range, 22 to 69 years) in Group 1, 32 patients (2 males, 30 females, mean age: 48.5±11.0; range, 22 to 73 years) in Group 2, and 35 patients (11 males, 24 females, mean age: 39.2±13.1; range, 22 to 67 years) in Group 3. Group 2 had significantly higher levels of FC compared to Group 3 (p< 0.05). The number of patients with positive FC values was similar between the three groups. Symptom severity scale and widespread pain index scores were significantly worse in Group 2 compared to Group 1 (p< 0.05). Conclusion: Irritable bowel syndrome usually coexists in many patients with FMS, and this may cause a misdiagnosis or delay in the diagnosis of organic gastrointestinal conditions. The value of FC in screening and diagnosis of organic disease in FMS patients needs further evaluation. An erratum has been published for this article : https://archivesofrheumatology.org/index.php/pub/issue/view/106/34